Water Delivery Quality and Automatic Control Modes in Irrigation Canals. A Case Study. - Rijo, Manuel (2016)
Regarding canal management modernization, water savings and water delivery quality, the study presents two automatic canal control approaches of the PI (Proportional and Integral) type: the distant and the local downstream control modes. The two PI controllers are defined, tuned and tested using an hydraulic unsteady flow simulation model, particularly suitable for canal control studies. The PI control parameters are tuned using optimization tools. The simulations are done for a Portuguese prototype canal and the PI controllers are analyzed and compared considering a demand-oriented-canal operation. The paper presents and analyzes the two control modes answers for five different offtake types – gate controlled weir, gate controlled orifice, weir with or without adjustable height and automatic flow adjustable offtake. The simulation results are compared using water volumes performance indicators (considering the demanded, supplied and the effectives water volumes) and a time indicator, defined taking into account the time during which the demand discharges are effective discharges. Regarding water savings, the simulation results for the five offtake types prove that the local downstream control gives the best results (no water operational losses) and that the distant downstream control presents worse results in connection with the automatic flow adjustable offtakes. Considering the water volumes and time performance indicators, the best results are obtained for the automatic flow adjustable offtakes and the worse for the gate controlled orifices, followed by the weir with adjustable height.